DEVELOPMENT OF SOCCER PASSING TRAINING MODELS WITH PLAY METHOD FOR BASE SCHOOL BEGINNERS - Mahfud, Imam; Fahrizqi, Eko Bagus (JOURNAL SPORTINDO, 2022)
The problem in this study is the low level of mastery of passing skills in the game of football. The objective to be achieved in this research and development is to produce a passing training model product with the playing method in a soccer game. This research uses the Research Development (RD) method of (Borg and Gall, 1983: 775). The subjects in this study were elementary school students in Labuhan Ratu District. The stages in this research are: needs analysis, expert evaluation (initial product evaluation), small group testing, and large group testing (field testing). The effectiveness of this development product is based on the assessment of 3 football experts, namely 2 lecturers soccer and 1 soccer coach. The value obtained is 82.6 which is declared valid and is suitable for use. Based on the results of the development it can be concluded: (1) The developed training model can be applied in the passing skill training process (2) The passing exercise model with this play method can improve students' passing skills, (3) As a contribution to education, especially in the field of football.